The Change Possibilities of Students’ Critical Thinking Skills and Dispositions - Rimienė, Vaiva (Acta Paedagogica Vilnensia, 2006)
The object of the research is cognitive and motivational aspects of critical thinking. This article presents the conception of critical thinking, views critical thinking researches in the world, and analyses some possibilities to develop it. Critical thinking defined as a cognitive process, a purposeful self-regulatory judgement that has two components: cognitive skills and motivational component (dispositions). Psychologists in USA, Canada, Western Europe study critical thinking and developed some methods to measure it. Here, in Lithuania, critical thinking wasn’t studied exhaustively. This article presents results of formative experiment that was pointed to developing critical thinking and carried out in Vilnius Pedagogical University. The program of critical thinking was based on the ideas of humanistic psychology and meaningful learning. The CCTST and CCTDI were used in this research. The author analyses results, draws conclusions, discusses possibilities of developing students’ critical thinking.